Pathology of Tnf-deficient mice infected with Plasmodium chabaudi adami 408XZ - Hernández Valladares, M.; Naessens, Jan; Musoke, A.J.; Sekikawa, K.; Rihet, P.; Ole-MoiYoi, O.K.; Busher, P.; Iraqi, F.A. (Elsevier, 2006)
Tumor necrosis factor alpha (Tnf) plays a pleiotropic role in murine malaria. Some investigations have correlated Tnf with hypothermia, hyperlactatemia, hypoglycemia, and a suppression of the erythropoietic response, although others have not. In this study, we have evaluated parasitemia, survival rate and several pathological features in C57BL/6JTnf−/− and C57BL/6JTnf+/+ mice after infection with Plasmodium chabaudi adami 408XZ. Compared to the C57BL/6JTnf+/+ mice, C57BL/6JTnf−/− mice showed increased parasitemia and decreased survival rate, whereas blood glucose, blood lactate and body weight were not significantly different. However, C57BL/6JTnf−/− mice suffered significantly more from severe anemia and hypothermia than C57BL/6JTnf+/+ mice. These results suggest that Tnf is an important mediator of parasite control, but not of anemia development. We hypothesize that the high mortality observed in the Tnf knock-out mice is due to increased anemia and pathology as a direct result of increased levels of parasitemia.